Material didáctico reciclado para el desarrollo del pensamiento lógico matemático en niños de nivel inicial de la Unidad Educativa Intercultural Bilingüe “Siete de Mayo”, de la comunidad Rodeopamba parroquia Julio Moreno, período académico 2018-2019 - Calderon Mena, Ximena Isabel (2019)
In the present research work, as a purpose, the elaboration of didactic material, with recycled elements as strategy for development of skills in the logical mathematical field of the children of the Initial Level, mathematical logical thinking begins to develop in the child from an early age. Methodology. The focus of the research was qualitative, the type of research was explanatory, the intervener population was 46 among children, teachers and parents, the techniques applied were: observation instrument record and checklist, the interview instrument script. The procedure for the data collection was to observe if the materials that the classroom teaching materials are sufficient or insufficient, as well as to consult the teachers, were observed the development of the skills of the manipulation of the didactic resources elaborated. Results The theoretical foundations were systematized, the process and resources for the elaboration of didactic materials was determined, the use and manipulation of the elaborated resource was made, Conclusion. In this research work was developed teaching materials, with recycled plastic elements, cartons, wood, lids, glass bottles, chips, as a strategy for developing skills in the logical mathematical field of children of the Initial Level of the Intercultural Bilingual Educational Unit "May 7". Keywords: Didactic material, recycled elements, thinking, mathematical logic, skills, initial level